Study on thermodynamic properties of MTBE/alcohol binary mixtures using nonlinear models and molecular interaction using spectroscopic approach - Thanusha, Thanihaik Kumaar (2017)
Over the years, fuel additive oxygenates have attracted a great interest due to the increasing environmental concern and fuel demand. Binary fuel oxygenate mixtures are believed to increase the performance of engine compared to pure fuel oxygenates. Thus, they are expected to reduce emission from vehicles. The problem that lies in obtaining the new formulation of binary fuel oxygenate mixtures is lack of data on their complete thermodynamic properties. Problems may arise in determining proper fuel blend or process design calculations when the thermodynamic properties are not known. There is also lacking in study on nonlinear models for the prediction of density and viscosity of the mixtures. In addition, it is also essential to know about the presence of molecular interaction of these binary mixtures to determine their stability when blended with gasoline. The binary mixtures of MTBE with ethanol, 1-propanol and 1-butanol are considered in this study due to their octane enhancing ability. Density and viscosity of MTBE with ethanol, 1-propanol and 1-butanol mixtures at temperatures 30 °C, 35 °C, 40 °C and 45 °C have been measured at selected range of composition. The density data are correlated with Jouyban-Acree model, whereas the viscosity data are correlated with Grunberg-Nissan, McAllister, Ausländer and Jouyban-Acree model. The model parameters are computed using least-square method. The excess molar volume and viscosity deviation are calculated from the experimental data and correlated with Redlich-Kister model. The observed variation in the excess functions in terms of composition and temperature, are discussed in terms of molecular interaction due to physical and chemical effect between the unlike molecules. Attenuated total reflectance-fourier transform infrared (ATR-FTIR) and proton nuclear magnetic resonance (1H-NMR) spectroscopy analysis was also done to provide evidence on the molecular interactions taking place in the mixtures. The presence of interaction was confirmed with change in band shift and difference in peak intensity of the binary mixtures and pure components. The results concluded that Jouyban-Acree model was a precise model for density measurement of the three mixtures having standard deviation in the range of 0.00028 to 0.00066, whereas Ausländer model has given good accuracy for viscosity measurement. ATR-FTIR and 1H-NMR analysis and excess properties of the binary mixtures shows that there may be strong interaction present between the components in the binary mixtures. The two possible interactions observed in the binary mixtures were hydrogen bond formation and geometrical fitting between the components in the binary mixtures.